Telehealth for Addressing Sexual and Reproductive Health and Rights Needs During the COVID-19 Pandemic and Beyond: A Hybrid Telemedicine-Community Accompaniment Model for Abortion and Contraception Services in Pakistan - Shaikh, Irum; Küng, Stephanie Andrea; Aziz, Hina; Sabir, Samina; Shabbir, Ghulam; Ahmed, Mukhtar; Dabash, Rasha (Frontiers in Global Women's Health, 2021)
The COVID-19 pandemic led overburdened health care systems to deprioritize essential sexual and reproductive healthcare, including abortion and contraception care, while accelerating shifts in healthcare delivery to digital technologies. However, in many countries, including Pakistan, inequalities in access to digital technologies remain, presenting an opportunity for interventions that both increase access to deprioritized sexual and reproductive health and rights (SRHR) services and overcome the digital divide in delivering digital solutions to those in need of SRHR services. In June 2020, Ipas Pakistan partnered with Sehat Kahani (SK), a local health care NGO and telehealth service, and an existing network of Lady Health Workers (LHWs) to launch a novel hybrid telemedicine-community accompaniment pilot. The model linked women via LHWs with mobile devices to online providers for telemedicine consultations for SRH, including abortion services, contraception, and other gynecological consultations. In June 2020, we trained 98 LHWs and 22 telehealth doctors. Between June 2020 and March 2021, a total of 176 women were referred by LHWs for telehealth consultations. Among women who received abortion services, nearly all (90%) reported complete uterine evacuation. No serious adverse events were reported. Overall satisfaction was high; 81% reported being satisfied, and 86% said it is likely they would recommend the telehealth service to others. Data show that the provision of SRHR services via a telehealth-accompaniment model can be successfully implemented in Pakistan. Outcome data show high satisfaction and good clinical outcomes for women accessing care through this model. However, more data are needed to understand the full potential of this model. Barriers to digital health models, such as poor or inconsistent internet access, remain in places like Pakistan, especially in rural settings. This approach has its limitations but should be considered as an option in settings with similarly established community health networks and inequitable access to digital health.